The Royal privilege registeres in the council of Segovia. Characteristics of a Medieval process of a legal and administrative continuity - Juárez Valero, Eduardo (Cuadernos de Historia del Derecho, 2021)
During the research process related to the MOOC The geography of the stroke: from the exploration of historical paleography to calligraphic creativity developed by the Department of Librarianship and Information Science of UC3M, working with notarial signs linked to the process of documentary validation, we discovered two medieval privilege register codices created by Council of Segovia at the end of 15th Century. We decided to study these codices in depth, because Isabel I, who ordered the creation of these books, decided to order a legislative process on the same issue ten years later, valid for the next four centuries.